Characteristics, surgical treatment, and outcomes of injuries involving the tarsus in greyhounds - Biggo, Morgan R.; Jones, Stephen C.; Wanstrath, Audrey W.; Tinga, Selena; Dyce, Jonathan; Carson, Brittney A.; Schaul, Kelsey; Follette, Christelle M.; Kieves, Nina R. (Frontiers in Veterinary Science, 2023)
Abstract Objective: The first objective of this study was to describe the type of tarsal injuries sustained, surgery performed, and postoperative complications in greyhounds presenting to a single veterinary hospital. An additional objective of the study was to determine the surgical site infection (SSI) and explantation rate and if any variables were associated with an increased risk of SSI and/or explantation. Animals: 116 greyhounds receiving surgical intervention for a tarsal injury. Proceures: Medical records from a single veterinary referral hospital were reviewed retrospectively. Data retrieved included signalment, details regarding the injury, surgical intervention, concurrent castration, surgical/anesthesia times, postoperative management, time to healing, and postoperative complications. In cases that underwent explantation, cause, time from initial surgery, and risk factors were evaluated. Results: The most frequently diagnosed tarsal injuries were fracture of the central tarsal bone (CTB; 57.8%), calcaneal fracture (56.9%) and proximal intertarsal subluxation (34.5%). The most common injury combination was a CTB fracture with a calcaneal fracture (31.9%). In total 115 (99.1%) survived to discharge. Of these, 46 (40.0%) were diagnosed with an SSI and 59 (51.3%) underwent explantation. The most common indication for explantation was SSI. Concurrent medial and lateral surgical approaches was found to be associated with an increased likelihood of SSI and explantation. Clinical Relevance: Practitioners performing surgical intervention for tarsal injuries in greyhounds should be aware of the high SSI rate and likelihood that explantation will be required. This risk is elevated for injuries requiring a bilateral surgical approach.